KUR'AN-I KERİM'DE TAĞYİR KAVRAMININ SEMANTİK ANALİZİ - YILDIRIM, ALİ (Fırat Üniveristesi, 2014)
Bir toplumun dili o toplumun dünya görüşünü yansıtmaktadır. Bu nedenle dilde meydana gelen değişim o toplumun dünya görüşünde meydana gelen değişimi yansıtmaktadır. Kur'an-ı Kerim de indiği toplumun dili olan Arapçayı kullanmıştır. Vahiy dili kullandığı kelimeleri kendi inanç yapısının semantik alanı içinde yeni bir anlam ile buluşturmuştur. Kur'an'daki önemli kavramlardan birisi olan 'tağyir'in hangi anlamlarda kullanıldığını tespit etmek, ilâhî hitabın anlaşılmasına katkıda bulunacaktır. Bu tespit, kavramın metin içi ve metin dışı bağlamını dikkate almak ile mümkün olacaktır. Kelimenin ilk anlamından başlayarak vahiy sürecinde kazanmış olduğu yeni anlamlara geçişinin seyrini bilmek sözden kastedileni anlamamızı sağlayacaktır. Ayrıca bu kavrama müfessirlerin bakışı da verilecek tağyirin anlamı ve mahiyeti hakkında geniş bilgi sunulacaktır. Anahtar Kelimeler: Kur'an, Tağyir, Semantik, Birey, Toplum.

Language of each society reflects its world-view. That is the reason why changes in language reflects changes in the world-view of the same society. In Holy Qur'an Arabic, the language of the society to which it sent for is used. The words used in theological language includes the cultural codes of the refused belief system. Revelation language collected the words that it use with the semantic field of their own belief system and changed them into new meanings. To determine the different meanings of one of the most important term the 'tağyir' in Holy Qur'an will be helpful to in understanding the theological adres. This determination will be possible in condition of giving importance to the textual and social background of the meaning of this term. Beginning from the first usage of the word and by knowing the history of its transition to the gaining the new meanings will be helpfull for us to understand what aimed by this word. In addition, Islamic thinkers' outlook on this term will be explained and extensive information about the meaning and importance of 'the stone wool ' will be presented. Key Words: Quran, The stone wool, Semantic, İndividual, Society.
Quran the Holy Quran is the stone wool semantic analysis of the concept
Keywords: Din